Advancing high-quality development in China: Unraveling the dynamics, disparities, and determinants of inclusive green growth at the prefecture level - Yufei Ren; Xinna He; Qunou Jiang; Fan Zhang; Bitian Zhang (Ecological Indicators)
Inclusive green growth (IGG), which underscores the delicate balance between economic expansion, ecological sustainability, and social well-being, has garnered substantial scholarly attention. Despite China’s remarkable economic growth in recent decades, this rapid development has also given rise to significant social and environmental challenges. Thus, advancing IGG is pivotal for ensuring China’s transition toward high-quality, sustainable development. Here, a novel evaluation framework of IGG is established by incorporating the nexus between urban production and governance. Our approach combines a two-stage network SBM model with a coupling coordination degree model, allowing for a comprehensive assessment of IGG across 281 Chinese prefecture-level cities from 2006 to 2019. The spatiotemporal variations and regional disparities in IGG are analyzed using the Dagum Gini model. Furthermore, we employ a panel quantile model and a spatial panel regression model to explore the mechanisms through which new-type urbanization (NTU) and other socio-economic factors influence IGG, with particular attention to individual heterogeneity, temporal dynamics, and spatial spillover effects. The findings reveal that although urban IGG in China has generally trended upward, substantial potential for further improvement remains. High-IGG cities are concentrated in the eastern region, but the gap between cities is gradually narrowing. The panel quantile model demonstrates that NTU and its components positively influence urban IGG, though the impact varies considerably across cities with different IGG levels. Additionally, temporal heterogeneity and spatial econometric analyses indicate that the influence of NTU on IGG is dynamic and exhibits significant spatial spillover effects. The policy implications highlight the importance of tailored regional strategies to promote green technology adoption, industrial upgrading, and inclusive public services, particularly in underdeveloped regions.